1973
DOI: 10.1139/v73-587
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Lycomarasmin

Abstract: Cultures of Fusarium oxysporum Schl. emend. Sny. et Hans. f lycopersici (Sacc.) Sny. et Hans. grown on a liquid medium with glucose as the principal carbon source produce, among other products, the phytotoxin lycomarasmin. Acid hydrolysis of lycomarasmin results in the formation of aspartic acid, glycine, and pyruvic acid. Tracer studies showed that glycine-U-I4C, L-serine-U-14C, DL-aspartic acid-4-14C, DL-alanine-1-14C, and glucose-U-14C served as relatively efficient precursors of the lycomarasmin molecule. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The mixture was stirred at room temperature, and the reaction was monitored by TLC [light petroleum-thy1 acetate (3: l)] until the reaction was complete; anhydrous diethyl ether was then added, the mixture was filtered and evaporated, and the residue was purified by flash column chromatography [light petroleum-ethyl acetate (3: l)] to give compound (9) as a solid in quantitative yield, m.p. 215 (10) and (lla and b).-To a solution of compound (9) (30 mg) in ethanol (20 ml) was added Pt02*2H20 (6 mg) and the mixture was hydrogenated at 30 "C and 10°C respectively. The catalyst was filtered off and the solvent was removed to give a mixture of compounds (lla) and (llb) (30 "C) and a mixture of compounds (lo), (lla), and (llb) (10 "C), both in quantitative yield.…”
Section: Oxidation Of Compound (8) With Pcc To Compound (9)mentioning
confidence: 99%
“…The mixture was stirred at room temperature, and the reaction was monitored by TLC [light petroleum-thy1 acetate (3: l)] until the reaction was complete; anhydrous diethyl ether was then added, the mixture was filtered and evaporated, and the residue was purified by flash column chromatography [light petroleum-ethyl acetate (3: l)] to give compound (9) as a solid in quantitative yield, m.p. 215 (10) and (lla and b).-To a solution of compound (9) (30 mg) in ethanol (20 ml) was added Pt02*2H20 (6 mg) and the mixture was hydrogenated at 30 "C and 10°C respectively. The catalyst was filtered off and the solvent was removed to give a mixture of compounds (lla) and (llb) (30 "C) and a mixture of compounds (lo), (lla), and (llb) (10 "C), both in quantitative yield.…”
Section: Oxidation Of Compound (8) With Pcc To Compound (9)mentioning
confidence: 99%
“…Melonis , and P. teres. , which were originally shown to cause plants to wilt. AMA was first isolated from A. oryzae in 1965 . Later, AMA was further found to inhibit angiotensin-converting enzymes through its metal-chelating activity. , As a phytotoxin, AMA was found to participate in the interaction with the host to promote fungi’s growth.…”
Section: Introductionmentioning
confidence: 99%
“…Although many synthetic studies toward AMA have been reported, the biosynthesis of AMA has yet to be elucidated. Previously, l -serine and d , l -aspartic acid were proven to serve as possible precursors of lycomarasmine through 14 C labeling studies . In 1991, a 14 C labeling experiment also indicated that toxin A ( 3 ) was the biosynthetic precursor of AMA .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation